Odpowiedzi

2010-01-14T19:11:16+01:00
1) 5x+3y=0
-x-2y=7 /*(-5)

5x+3y=0
5x+10y = -35 /:5

5x+3y=0
x+10y=-7

5x+3y=0
x=-7-10y

5 *(-7-10y) + 3y= 0
x=-7-10y

-35-50y +3y = 0
x=-7-10y

-47y = 35 /;(-47)
x=-7-10y

y = - 35/47
x = -7 - 10*(-35/47) = -7 + 350/47 = -7 + 7 21/47 = 21/47

2) 3u+2u=2/:(-2)
5u+4u=6

-3/2u - u = -1
5u+4u=6

-6/3u=-1 /:(-6/3)
9u=6 /:9

u = -1 * (-3/6) = 3/6 = 1/3
u = 6/9 = 2/3

3) 3s+5t=-6 /. (-2)
1,5s-2t=-3 /. (-2)

-6s - 10t = 12
-3s + 4t = 6 /*(-2)

-6s-10t=12
6s - 8t = -12 +
_______________

-18t = 0
t=0

6s - 8*0 = -12
6s=12 /:6
s=2

t=0
s=2